Characterizing the effects of in-situ sensitization on stress corrosion cracking of austenitic steels in supercritical water. (1st January 2019) - Chen, Kai; Wang, Jiamei; Du, Donghai; Guo, Xianglong; Zhang, Lefu
Abstract: This work compared the stress corrosion cracking (SCC) susceptibility of two austenitic alloys in supercritical water (SCW), and revealed the quantitative difference of SCC growth rates through scanning transmission electron microscopy (STEM). Results showed that in-situ sensitization and creep occurred on the specimens during the SCC tests in SCW environment. Higher degree of Cr-depletion at the grain boundary ahead of the SCC crack tip was identified in the Fe- 25 Cr steel specimen, which has suffered severer in-situ sensitization because of the lower Cr content than the Ni- 29.3 Cr alloy specimen, and this in turn increased the creep susceptibility. Graphical abstract: Unlabelled Image